Pengembangan media pembelajaran “alphabet flip” untuk meningkatkan kemampuan keaksaraan anak usia 4-5 tahun - Khusniyah, Syarifatul (Maliki Interdisciplinary Journal, 2025)
This study aims to develop an interactive learning media called “Alphabet Flip” to improve literacy skills in children aged 4–5 years. The development of this media was motivated by the observed low interest and ability of young children in literacy-related activities, compounded by the lack of concrete, enjoyable, and age-appropriate learning tools. The research employed the Research and Development (RnD) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. “Alphabet Flip” is a flip board designed with engaging visual elements, featuring activities such as tracing letters, word writing, solving mazes, and introducing healthcare professions as contextual themes. Expert validation results indicated that the media is highly appropriate for classroom use. Trial implementation at TK Muslimat NU 2 Singosari showed positive student responses and noticeable improvement in letter recognition, distinguishing uppercase and lowercase letters, and writing simple words. Final evaluations confirmed the media’s feasibility, practicality, and effectiveness in enhancing early literacy skills in young children. This media also fosters an enjoyable and meaningful learning atmosphere through multisensory and contextual approaches.